Exchange Rate Dynamics in Nigeria: Does Government Expenditure Matters? - Kanwanye, Hilary Temofeh; Oseni, Mohammed Sanusi (Social Science Research, 2022)
This paper examined the relationship between government expenditure and exchange rate in Nigeria using annual time series data from 1980 to 2020 obtained from the Central Bank of Nigeria Statistical Bulletin 2021. An Autoregressive Distributed Lag (ARDL) model was specified and estimated using ordinary least squares to analyse the relationship. The results show that government and private consumption expenditures, domestic investment activities, and interest rate led to a significant deterioration of the exchange rate over the period under investigation. Openness of the Nigerian economy to trade significantly spurred appreciation of exchange rate while foreign investment activities had insignificant effect on exchange rate in the country. Result also showed that government consumption expenditure complemented private consumption expenditure and affected real exchange rate via consumption-tilting channel. It was recommended amongst others, that government expenditure be channelled via appropriate fiscal and exchange rate policies, to domestically produced commodities, rather than imports, especially when such commodities are available in the country.